KONSEP PERTANIAN PULAU-PULAU KECIL BERBASIS GUGUS PULAU MENGHADAPI PERUBAHAN IKLIM GLOBAL DI PROVINSI MALUKU - Agustinus Kastanya (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Indonesia has already agreed to and submitted Intended Nationally Determined Contributions (INDC) to the UNFCCC, to reduce emission gases by 29% on its own and by 41% with outside help by 2030. This step follows the Paris Agreement (COP 21) to reduce world emission gases to prevent the earth warming by 20C . Maluku is characterized by small islands, narrow and short watersheds and needs an innovative approach to development. Multi landscape based development of small islands means using island clusters, watersheds, ecological conditions and socio-economic conditions. An agricultural concept for small islands based on multi landscape plans like green economics has been developed in 3 base concepts : (1) conceptual framework; (2) macro concept framework; (3) micro concept framework. The multi landscape format integrates water catchments and RTRWP/K which are organized into the smallest management units in accordance with indigenous rights. The complete landscape is managed using an agroforestry system for conservation of the watersheds, islands, cluster groups and seas. Thus, the agricultural concept can deliver productivity and services to meet the needs of the community and the environment as well as for mitigation of and adaptation to climate change.